Physiological mechanisms of drought-induced tree die-off in relation to carbon, hydraulic and respiratory stress in a drought-tolerant woody plant - Shin-Taro Saiki (Nature Portfolio, 2017)
Abstract Drought-induced tree die-off related to climate change is occurring worldwide and affects the carbon stocks and biodiversity in forest ecosystems. Hydraulic failure and carbon starvation are two commonly proposed mechanisms for drought-induced tree die-off. Here, we show that inhibited branchlet respiration and soil-to-leaf hydraulic conductance, likely caused by cell damage, occur prior to hydraulic failure (xylem embolism) and carbon starvation (exhaustion of stored carbon in sapwood) in a drought-tolerant woody species, Rhaphiolepis wrightiana Maxim. The ratio of the total leaf area to the twig sap area was used as a health indicator after drought damage. Six adult trees with different levels of tree health and one dead adult tree were selected. Two individuals having the worst and second worst health among the six live trees died three months after our study was conducted. Soil-to-leaf hydraulic conductance and leaf gas exchange rates decreased linearly as tree health declined, whereas xylem cavitation and total non-structural carbon remained unchanged in the branchlets except in the dead and most unhealthy trees. Respiration rates and the number of living cells in the sapwood decreased linearly as tree health declined. This study is the first report on the importance of dehydration tolerance and respiration maintenance in living cells.